The Effect of the Problem-Based Learning Model on Improving Elementary School Students’ Numeracy Skills: A Literature Review - Ana Ramadani; St. Sri Susilawati (PT. Lontara Digitech Indonesia, 2025)
This study aims to determine the effectiveness of the Problem-Based Learning model in improving elementary school students’ numeracy skills. The research method used was descriptive qualitative with a literature review approach. The results of the study showed that the Problem-Based Learning model was proven effective in improving students’ numeracy skills. There was a significant difference between the literacy skills of students who used the Problem-Based Learning model and those who received conventional learning. The Problem-Based Learning model is designed to train students to solve problems critically and creatively, as well as to improve their numeracy skills. The findings of this study are supported by expert opinions stating that the Problem-Based Learning model is relevant for improving students’ literacy and numeracy skills. The results of this study can serve as a consideration for teachers and related parties in developing and implementing more effective learning models to improve students’ basic skills.